Endoscopic myringoplasty: comparison of double layer cartilage-perichondrium graft and single fascia grafting - Zheng cai Lou (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective To compare surgical results of endoscopic myringoplasty using double layer cartilage-perichondrium grafts versus single fascia grafts. Study design Prospective, randomized, controlled. Setting University-affiliated teaching hospital. Subjects and methods In total,134 patients who underwent endoscopic myringoplasty were included in this study. Patients in group A received a double layer tragal cartilage-perichondrium graft and those in group B received a temporal muscle fascia graft. The groups were compared with respect to the pre- and postoperative air-bone gap (ABG) and the graft success rate. Results The graft success rate was 98.5% (66/67) in the Group A and 94.0% (63/67) in the Group B at 6 months, the difference wasn’t statistically significant (p = 0.362). However, the graft success rate was 97.0% (65/67) in the Group A and 85.1% (57/67) in the Group B at 12 months, the difference was statistically significant (p = 0.034). In addition, only one patient (1.49%) had small keratin pearls in the Group A, no patients developed cholesteatoma of middle ear in either group. Conclusions The endoscopic double layer perichondrium-cartilage graft technique is feasible for repairing medium or larger perforations, it has a better long-term graft success rate and less operative time compared with the single layer fascia graft technique. However, long-term hearing outcomes were the same for the single and double layer closure techniques.